PENERAPAN METODE PEMBELAJARAN TALKING STICK DALAM UPAYA MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PKN KELAS VII-2 SMP NEGERI 3 KOTA TEBING TINGGI - Herlina Manurung (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This purposes of this research is to improve learning result on civics subject  through talking stick method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class VII-2 SMPNegeri 3Tebing Tinggi which amounted to 36 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the inquiry method of civics subjects can improve student learning result characterized by increased mastery learning students, namely cycle I (80,56%), cycle II (88,89 %) and complete learn the clasical equal to 88.23 %. Key words: Talking stick, Civic, Learning outcomes